Problemi informatizacije Slovenije - Trček, Franc (Teorija in praksa, 2000)
Level of informatisation becomes main comparative indicator of development of postindustrial countries, depending upon informatisation policy at different territorial levels. The article discusses the state of informatisation in Slovenia. The estimation is based on analysis of public speeches given by political authority representatives, on analaysis of advertising and analysis of empirical data and indicators on informatisation. The analysis shows that Slovenia lacks an policy of informatisation as a part of developmental policy. That is also the main reason for delayed introduction of tele-services and tele-working in Slovenia.
Keywords: Informacijska družba; Information society; Internet; informatizacija; Slovenia; Slovenija; družbeni razvoj